TIGIT regulates CD4+ T cell immunity against polymicrobial sepsis - Zhong, Xuexin; Xie, Haiping; Wang, Shuang; Ren, Tingting; Chen, Junlin; Huang, Yuefang; Yang, Niansheng (Frontiers in Immunology, 2024)
Sepsis is one of the major causes of death and increased health care burden in modern intensive care units. Immune checkpoints have been prompted to be key modulators of T cell activation, T cell tolerance and T cell exhaustion. This study was designed to investigate the role of the negative immune checkpoint, T cell immunoglobulin and ITIM domain (TIGIT), in the early stage of sepsis.An experimental murine model of sepsis was developed by cecal ligation and puncture (CLP). TIGIT and CD155 expression in splenocytes at different time points were assessed using flow cytometry. And the phenotypes of TIGIT-deficient (TIGIT -/-) and wild-type (WT) mice were evaluated to explore the engagement of TIGIT in the acute phase of sepsis. In addition, the characteristics were also evaluated in the WT septic mice pretreated with anti-TIGIT antibody. TIGIT and CD155 expression in tissues was measured using real-time quantitative PCR and immunofluorescence staining. Proliferation and effector function of splenic immune cells were evaluated by flow cytometry. Clinical severity and tissue injury were scored to evaluate the function of TIGIT on sepsis. Additionally, tissue injury biomarkers in peripheral blood, as well as bacterial load in peritoneal lavage fluid and liver were also measured.The expression of TIGIT in splenic T cells and NK cells was significantly elevated at 24 hours post CLP.TIGIT and CD155 mRNA levels were upregulated in sepsis-involved organs when mice were challenged with CLP. In CLP-induced sepsis, CD4 + T cells from TIGIT -/-mice shown increased proliferation potency and cytokine production when compared with that from WT mice. Meanwhile, innate immune system was mobilized in TIGIT -/-mice as indicated by increased proportion of neutrophils and macrophages with potent effector function. In addition, tissue injury and bacteria burden in the peritoneal cavity and liver was reduced in TIGIT -/-mice with CLP induced sepsis. Similar results were observed in mice treated with anti-TIGIT antibody.TIGIT modulates CD4 + T cell response against polymicrobial sepsis, suggesting that TIGIT could serve as a potential therapeutic target for sepsis.